Galanin expression is down-regulated in patients with gastric cancer - Lei Zhang; Penghua Fang; Chenghua Chai; Lijuan Shao; Haiyan Mao; Dawei Qiao; Guimei Kong; Xiaoyun Dong; Mingyi Shi; Zhenwen Zhang; Ping Bo (Journal of International Medical Research, 2019)
Objective To investigate whether galanin and its three receptors (Gal-R1, Gal-R2, Gal-R3) contribute to development of gastric cancer. Methods Preoperative and postoperative fasting venous blood samples were collected from 34 patients with gastric cancer and 13 healthy individuals. Plasma galanin contents, as well as expression levels of galanin and its receptors, were quantitatively examined in a cohort of human gastric cancer tissues and corresponding adjacent tissues. Results Statistically significantly lower galanin levels were found in the preoperative samples from patients with gastric cancer, compared with postoperative samples from these same patients, as well as with samples from healthy donors. Furthermore, galanin and Gal-R1 expression levels were dramatically reduced in gastric cancer tissues, compared with corresponding adjacent tissues, whereas Gal-R2 and Gal-R3 levels remained unchanged. Furthermore, galanin mRNA and protein expression levels in the preoperative samples from patients with gastric cancer were significantly correlated with lymph node metastasis, tumor node metastasis stage, and size of the gastric cancer. Conclusions Overall levels of galanin and Gal-R1 expression were down-regulated in patients with gastric cancer; local levels were also specifically downregulated in gastric cancer tissues. Galanin and its receptor, Gal-R1, may contribute to development of gastric cancer.